Creative Analysis of Innovation as a Catalizer of Socialization of Structural Change - DRUZHYNINA, Viktoriia; VIEDIENINA, Yuliia; SAKUN, Lesia; LIKHONOSOVA, Ganna (European Journal of Sustainable Development, 2020)
The multiple analysis of rate of dependency between innovative processes and structural labour market changes in the form of evolution in sector of employment was exposed in the article. It has been proved that the impact of innovations on the labour market can be considered, on the one hand, as a part of multi-factor socio-economic macro-, meso-, micro-level systems, which makes a direct or indirect impact on state of other elements of system and which is under its influence at this time; on the other hand, as an open, dynamic, flexible system, functioning of which leads to socio-economic resources development. The definition of labour market has been suggested as a system of socio-economic relations between workers, employers and society (organizations and institutes) for realization of ability to work, supporting social guarantees, approximation of parties’ interests of labour relations, state`s interests, legal control of terms of employment etc. The analysis of structural changes, which take place in the labour market of different levels administrative territorial state`s structure by means of innovations, covers the period 2012-2017. The impact of innovations on employment is associated with `creative destruction` where innovations, on the one hand, ruin current workplaces and, on the other hand, create new ones. Analysis has demonstrated that employment increasing and related structural improvements are determined by kind of incorporated innovations. Organizational innovations have more impact on size and structure of employment, than technological ones. The practical importance of the research involves developing of methodological and practical aspects of choosing multiple approach in relation to innovation analysis as a determinant of structural labour market changes. The originality of the research is reflected in the comprehensive creative analysis of innovations from the point of view of activation of the youth labour market in Ukraine. The key factors of the low level of involvement of young citizens in the country’s economy and society are identified. The authors have suggested the prospects for the development of the youth labour market, the elimination of youth unemployment, which are conditioned by the peculiarities of the social condition and employment behaviour of young people. The need to study the experience of European countries is emphasized, where training in the working professions is well organized and the youth unemployment rate is the lowest in Europe. Distinctiveness. Conducted researches let to confirm attained results in relation to choosing implements for coping with current troubles and disproportions in society. Implementation of multiply approach of analysis and diagnostics of correlation of innovations and employment will make a direct impact on supporting living standards and progressive socio-economic state`s development. The monitoring of solidarity of actions of public communities, government agencies, enterprise structures will ensure attainment of active increasing of innovation technologies, high living standards level, that will offer some new opportunities for business environment in relation to labour productiveness maintaining method and equivalent income level from enterprise activity, will solve the unemployment and labour migration issues, create some new flexible forms of employment, increase the level of state`s competitiveness in global economy facilities. Key Words: creative analysing, diagnostics, employment of population, innovations, multiple approach